Coating Fe2O3 with graphene oxide for high-performance sodium-ion battery anode. (October 2016) - Li, Henan; Xu, Li; Sitinamaluwa, Hansinee; Wasalathilake, Kimal; Yan, Cheng
Abstract: Sodium-ion batteries (SIBs) have recently shown the potential to meet the demands for large scale energy storage needs as an attractive alternative to lithium-ion batteries due to the high abundance of sodium resources around the world. The major hurdle of SIBs resides in developing viable anode materials with a high energy density and an appropriately long cycle life. Here a simple and low-cost method for synthesizing Fe2 O3 /graphene oxide (Fe2 O3 /GO) composites made out of Fe2 O3 nanoparticles sandwiched between graphene oxide (GO) layers is reported. The unique structure of the Fe2 O3 /GO composites served a synergistic effect to alleviate the stress of Fe2 O3 nanoparticles, prevent nanoparticles aggregation, maintain the mechanical integrity of the electrode, and facilitate mass transfer of Na ions during batteries operating. Consequently, the Fe2 O3 /GO composites as anode for SIBs attained a reversible specific capacity of ca. 420 mAh g − 1 after 100 cycles at 0.1 C (1 C=1007 mA g −1 ) and a good rate capability at various current densities. Moreover, the Coulombic efficiency of the SIBs could rapidly increase in the early cycles. Due to the facile synthesis method and high electrochemical performance, the Fe2 O3 /GO composites would have a significant potential as anode materials for rechargeable SIBs. Highlights: A flexible interleaved Fe2 O3 /GO composite are used as anode materials for SIBs. GO can act as flexible but mechanically strong buffer to ease the stress. Fe2 O3 /GO composite can provide superior rate and exceptional electrochemical stability.